2015
DOI: 10.1039/c4ra16919k
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of copper nanoparticles in glycerol at room temperature: formation mechanism

Abstract: A copper sol is usually synthesized by the reduction of a copper precursor with a suitable reducing agent in the presence of a stabilizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…In Figure A(b), the peaks observed at 35.4, 37.6 and 41.3 eV due to the binding energies of W( 4f 7/2 ), W( 4f 5/2 ) and W( 5p 3/2 ) respectively, of W 6+ state . In Figure A(c), the main peak is shown at 530.5 eV for O ( 1 s ) and it can be deconvoluted into two peaks with broad at 530.3 and tail at 530.95 eV are assigned to the Cu−O of CuO and W−O of normalWnormalO3 respectively ,. By comparing the results with earlier reports,,, the present study does not show any OH − related signals in normalCnormalunormalWnormalO4 particles due to the OH − groups of PEG compensated the loss of oxygen during annealing.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In Figure A(b), the peaks observed at 35.4, 37.6 and 41.3 eV due to the binding energies of W( 4f 7/2 ), W( 4f 5/2 ) and W( 5p 3/2 ) respectively, of W 6+ state . In Figure A(c), the main peak is shown at 530.5 eV for O ( 1 s ) and it can be deconvoluted into two peaks with broad at 530.3 and tail at 530.95 eV are assigned to the Cu−O of CuO and W−O of normalWnormalO3 respectively ,. By comparing the results with earlier reports,,, the present study does not show any OH − related signals in normalCnormalunormalWnormalO4 particles due to the OH − groups of PEG compensated the loss of oxygen during annealing.…”
Section: Resultsmentioning
confidence: 94%
“…In Figure A(d), the peaks are shown centered at 934.2 eV and 953.9 eV due to Cu ( 2p 3/2 ) and Cu ( 2p 1/2 ) respectively, of CuWO 4. The shakeup satellite peaks are observed at 942.9 and 944.8 eV for Cu ( 2p 3/2 ) and at 963.3 eV for Cu ( 2p 1/2 ). These results confirmed that the phase pure normalCnormalunormalWnormalO4 synthesized at pH 5.3.…”
Section: Resultsmentioning
confidence: 95%
“…2a shows the CuCl 2 spectrum with a peak at 230 nm (Cu-Cu interaction) and a broad peak at 810 nm, assigned to the Cu-H 2 O interaction. 53 The CuNP curve at pH 1 (resulting from the synthesis) shows shoulder type peaks at 200, 242 and 300 nm. Additionally, a close up to the 300-600 nm region, exhibits a third peak at 390 nm, caused by the change in the surface plasmon resonance of CuNP and indicates the formation of copper nanoparticles.…”
Section: Synthesis Of Cunp and Rgo|cunpmentioning
confidence: 99%
“…[20] In contrast, long-alkyl-chain aminesf avor the stabilization of metal (and metal oxide) nanoparticles. [21] Presuming the formation of copper-basedn anoclusters under our reaction conditions, [22] TEM analyses of CuI in glycerol and in the presence of differenta mines were carried out ( Table S2 in the Supporting Information). Actually,t he formation of well-dispersed nanoparticles was observed in the presence of long-alkyl-chain amines,i ncluding ammonium derivatives (Figure 2).…”
Section: Resultsmentioning
confidence: 99%